Spectropolarimetric study of Mira-type variable stars - Fabas, Nicolas (2009)
Everything started back in 1978, with the discovery by McLean & Coyne of hydrogen emission lines, undergoing polarization, on the variable star Omicron Ceti (a.k.a. Mira). Those emissions seemed likely to be linked with a shockwave propagating through the stellar atmosphere. Further observations showed that emission -, and thus polarization -, lasted during 80% of luminosity variation period. According to shockwave theory, a magnetic field should appear just behind the shock front, inducing polarization, but this field has never been conclusively detected so far. Here, we present a full spectropolarimetric study (on the four Stokes parameters I,Q,U and V), made with instrument NARVAL at TBL (Telescope Bernard Lyot) in the French Pyrenees, aimed toward the complete characterization of the polarization behavior with respect to the shockwave intensity. The detected signatures are most probably of magnetic origin. Validerat; 20101217 (root)